The importance of stress coping strategies in the elderly (Research, Society and Development, 2021)
This work aims to carry out a literature review on the relationship between stress and the elderly, to emphasize the importance of coping strategies for stress in the elderly. The methodology used were book and article consultations, online search in research platforms such as SCIELO, PEPSIC, EBSCO and Academic Google, providing the reader with an understanding of what stress is, and how the elderly are perceived by society, its relationship in the elderly, what are the possible factors that can trigger it during old age and, finally, reinforce the importance of adequate coping strategies in combating stress in old age. It can be seen that stress is the body's response to a dangerous situation that prepares the body to flee or fight, this action causes tension and irritation where the body reacts to physical or psychological components when there is a situation that causes fear, excitement or confusion, which can affect anyone, regardless of gender and age, and many elderly people complain about extremely stressful situations that directly influence their way of perceiving and living life misperception of the situation, causing the elderly to have an inadequate response to stress. It was through this that it is understood that continuous changes that occur in different degrees and intensities and that are inherent to human development, being predictors of stress in old age, which can harm them in an extreme way.